A new class of estimators of finite population mean in sample surveys. Issue 6 (19th March 2017) - Singh, Housila P.; Pal, Surya Kant; Solanki, Ramkrishna S.
ABSTRACT: This article suggests the class of estimators of population mean of study variable using various parameters related to an auxiliary variable with its properties in simple random sampling. It has been identified that the some existing estimator/classes of estimators are members of suggested class. It has been found theoretically as well as empirically that the suggested class is better than the existing methods.